Nutrition related knowledge and attitudes of mothers and teachers of kindergarten children - Nese Ormanci; Saima Tasneem; Tugba Busra Caliskan (International Journal of Public Health Science (IJPHS), 2022)
Programs focusing on health and nutrition help ensure children’s early development. Nutrition knowledge of families and teachers has a significant impact on children’s eating habits and dietary patterns. Recently, there is an increase in the number of daycare schools in North Cyprus, offering services between 8 AM to 6 PM and provide two main meals and two snacks during the day. This study was carried out to understand the nutrition-related knowledge of kindergarten teachers and mothers of children aged 2-5 and their attitudes towards nutrition, and find the deficiencies in the knowledge and attitude of both groups as they significantly impact dietary habits of children. The 121 participants from the Kyrenia District, Turkish Republic of North Cyprus were enrolled, 79 were educators in the kindergarten and 42 were mothers. It was observed that there is no statistically significant difference between mothers' and teacher's knowledge and attitude of the nutritional content of foods. Our study also showed that though mothers were educated and possessed knowledge of nutrients yet their attitudes did not reflect it. Our study revealed that the current knowledge status of teachers and caregivers, as well as their attitudes towards various aspects of diet, are not sufficient to lay the foundation of healthy eating.